Current legal organization of judicial evidence and 'independent, objective' judges - A.S. Aleksandrov; A.A. Yunusov; N.N. Rybushkin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper proposes a solution to the fundamental problem of Russia’s legal and socio-economic development, which is related to establishing fair (objective and independent) trial. We believe that this problem can be successfully solved by changing the current criminal procedure and developing an adversarial organization of criminal proceedings. The main measures for the institutional judicial reform to achieve this goal were discussed. We consider it necessary to renounce the canons of the Soviet school of investigative criminal procedure and criminal procedural evidence. The main provisions of a new theory of criminal procedural (judicial) evidence, which is being developed in the Nizhny Novgorod school of proceduralists, were outlined. Among these provisions is the concept of judicial truth, the standards of proof of decisions taken in the course of criminal proceedings. Our own view on the process of formation of judicial evidence and facts, which should be taken as the basis for acts of law enforcement, was explained. The projects of judicial institutions responsible for bringing charges and the adversarial model of criminal procedure mechanism of bringing to criminal responsibility were built. In our opinion, the institution of cross-examination and direct interrogation must ensure the rule of judicial investigation over preliminary investigation. Otherwise, it is impossible to create an independent and objective criminal trial.